Size-controllable synthesis of polymeric iodine-carrying nanoparticles for medical CT imaging - Illert, Patrick; Wängler, Björn; Wängler, Carmen (Polymers for advanced technologies, 2017)
Iodine-carrying nanopolymers with particle sizes ranging from 30 to 930 nm were synthesized by microemulsion polymerization. 2-Methacryloyloxyethyl(2,3,5-triiodobenzoate) was used as the monomer. Different surfactants were tested to control the particle size. Cetyltrimethylammonium bromide and cetyltrimethylammonium chloride were used as cationic surfactants, and sodium oleate and sodium dodecyl sulfate acted as anionic surfactants. The influences of various reaction parameters, e.g. the amount of surfactant, amount of initiator, and the reaction temperature, were investigated. The particle size was highly adjustable through variation of the reaction parameters. The particles were imaged with an atomic force microscope. In addition, particle workup for further medical application was explored. The particles provided good visible computer tomography contrast. Copyright © 2017 John Wiley & Sons, Ltd.